2007
DOI: 10.1002/ijc.22790
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of dietary flavonoid intake and incidence of epithelial ovarian cancer

Abstract: Flavonoids are antioxidant compounds found in plants, including fruits, vegetables and tea. No prior prospective studies have examined the association between intake of flavonoids in the flavonol and flavone subclasses and ovarian cancer risk. We analyzed the association between intake of 5 common dietary flavonoids and incidence of epithelial ovarian cancer among 66,940 women in the Nurses' Health Study. We calculated each participant's intake of myricetin, kaempferol, quercetin, luteolin and apigenin from di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
180
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(191 citation statements)
references
References 62 publications
11
180
0
Order By: Relevance
“…Another case-control study in Scotland showed that there is a strong and linear inverse associations of flavonoids intake with colorectal cancer risk (45). A recent study showed that there was a significant decrease in incidence of ovarian cancer for the highest versus lowest quintile of luteolin intake (46).…”
Section: Discussionmentioning
confidence: 99%
“…Another case-control study in Scotland showed that there is a strong and linear inverse associations of flavonoids intake with colorectal cancer risk (45). A recent study showed that there was a significant decrease in incidence of ovarian cancer for the highest versus lowest quintile of luteolin intake (46).…”
Section: Discussionmentioning
confidence: 99%
“…A random effects model was used because of significant heterogeneity. On tea drinking and ovarian cancer, eight casecontrol studies (Byers et al, 1983;Miller et al, 1987;La Vecchia et al, 1992;Kuper et al, 2000;Tavani et al, 2001;Zhang et al, 2002;Jordan et al, 2004;Baker et al, 2007) and, including this study, five cohort studies (Zheng et al, 1996;Larsson and Wolk, 2005b;Gates et al, 2007;Silvera et al, 2007) have been conducted. Coffee drinking and ovarian cancer risk was investigated in 16 case-control studies (Trichopoulos et al, 1981;Hartge et al, 1982;Byers et al, 1983;Cramer et al, 1984;La Vecchia et al, 1984;Tzonou et al, 1984;Miller et al, 1987;Whittemore et al, 1988;Polychronopoulou et al, 1993;Kuper et al, 2000;Tavani et al, 2001;Jordan et al, 2004;Riman et al, 2004;Baker et al, 2007) and, including this study, five cohort studies (Snowdon and Phillips, 1984;Stensvold and Jacobsen, 1994;Larsson and Wolk, 2005a;Silvera et al, 2007).…”
Section: Meta-analysismentioning
confidence: 99%
“…Regardless, these results suggest that antilymphatics may be best given in conjunction with other compounds that prevent tumor growth. Previous work has shown that kaempferol consumption has been associated with reduced risk of developing many cancers (38)(39)(40) and has also been shown to reduce VEGF expression in human cancer cell lines (41,42). To our knowledge, this study is the first to report VEGFR inhibition and antilymphatic activity for kaempferol.…”
Section: Discussionmentioning
confidence: 56%